2015
DOI: 10.1179/1743284714y.0000000733
|View full text |Cite
|
Sign up to set email alerts
|

Nanoausferritic matrix of ductile iron

Abstract: Austempered ductile iron is known for its excellent mechanical properties resulting from special phase composition and austempering heat treatment. Typical microstructure consists of ferrite plates of micrometre size submerged in untransformed austenite matrix. It has been recently shown that by use of appropriate chemical composition of cast iron and well targeted heat treatment parameters, it is possible to reduce ferrite plates width to submicron or even nanometric size. This creates the potential to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Similar report was provided by Myszka, et al (2015) and Myszka, et al (2014) which tried to produce nanostructured ADI by austempering at lower bainitic transformation temperature range for a prolonged period and achieved a significant refinement of ferrite plates in less than 100 nm range. Putatunda et al (2015) in its investigation likewise developed ADI possessing microstructure at nano scale with the aid of high temperature deformation and subsequently, austempering of the ductile iron.…”
Section: Processing Techniques Of Nanostructured and Nanocomposite Austempered Ductile Ironssupporting
confidence: 69%
“…Similar report was provided by Myszka, et al (2015) and Myszka, et al (2014) which tried to produce nanostructured ADI by austempering at lower bainitic transformation temperature range for a prolonged period and achieved a significant refinement of ferrite plates in less than 100 nm range. Putatunda et al (2015) in its investigation likewise developed ADI possessing microstructure at nano scale with the aid of high temperature deformation and subsequently, austempering of the ductile iron.…”
Section: Processing Techniques Of Nanostructured and Nanocomposite Austempered Ductile Ironssupporting
confidence: 69%
“…Electron diffraction patterns analysis revealed that the microstructure consisted of thin bainitic ferrite plates separated by thin layers of retained austenite. In case of steels this kind of microstructure is called nanobainite [13][14][15], while in ductile iron we can speak of nanoausferrite [6,7]. The average width of ferritic plates was similar for both samples and it was 126 ± 13 nm and 116 ± 7 nm in ADI-1 and ADI-2, respectively.…”
Section: Resultsmentioning
confidence: 71%
“…One of directions of the research work was to produce the alloys with nanocrystalline microstructure and precisely designed phase composition [4][5][6][7]. However, to control the phase composition, especially the content of the retained austenite is not an easy task and needs application of the accurate methods of phases volume fraction determination.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, only slight changes in the graphite morphology were observed in the UST SG irons. Recently, it was found that thermomechanical treatment 34,35 or performing very long austempering time 36 could lead to evolution of a novel nano-scale ADI microstructure, with an exceptional combination of strength and ductility properties.…”
Section: Introductionmentioning
confidence: 99%